2017
DOI: 10.1016/j.foodchem.2016.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Variation of theanine, phenolic, and methylxanthine compounds in 21 cultivars of Camellia sinensis harvested in different seasons

Abstract: This is the first study to use chemometric methods to differentiate among 21 cultivars of Camellia sinensis from China and between leaves harvested at different times of the year using 30 compounds implicated in the taste and quality of tea. Unique patterns of catechin derivatives were observed among cultivars and across harvest seasons. C. sinensis var. pubilimba (You 510) differed from the cultivars of C. sinensis var. sinensis, with higher levels of theobromine, (+)-catechin, gallocatechin, gallocatechin ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 22 publications
3
35
0
3
Order By: Relevance
“…These studies indicated that theanine accumulation was dynamically regulated by seasons (Konishi and Takahashi, 1969; Takeo, 1981; Janet et al, 2015), light (Yang et al, 2012; Deng et al, 2013; Chen et al, 2017; Ji et al, 2018; Sano et al, 2018), nutrient levels (Takeo, 1981; Ruan et al, 2007; Ruan et al, 2010; Ruan et al, 2012; Huang et al, 2018; Kc et al, 2018; Zhu et al, 2019), hormones (Li et al, 2016a), developmental stages (Feldheim et al, 1986; Li et al, 2016b; Liu et al, 2017), and stress (Deng et al, 2012; Wang et al, 2016). Theanine accumulation is also highly tissue-and cultivar-dependent (Fang et al, 2017; Liu et al, 2017; Chen et al, 2018a; Chen et al, 2018b). Theanine accumulation, therefore, is dynamic and highly regulated.…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicated that theanine accumulation was dynamically regulated by seasons (Konishi and Takahashi, 1969; Takeo, 1981; Janet et al, 2015), light (Yang et al, 2012; Deng et al, 2013; Chen et al, 2017; Ji et al, 2018; Sano et al, 2018), nutrient levels (Takeo, 1981; Ruan et al, 2007; Ruan et al, 2010; Ruan et al, 2012; Huang et al, 2018; Kc et al, 2018; Zhu et al, 2019), hormones (Li et al, 2016a), developmental stages (Feldheim et al, 1986; Li et al, 2016b; Liu et al, 2017), and stress (Deng et al, 2012; Wang et al, 2016). Theanine accumulation is also highly tissue-and cultivar-dependent (Fang et al, 2017; Liu et al, 2017; Chen et al, 2018a; Chen et al, 2018b). Theanine accumulation, therefore, is dynamic and highly regulated.…”
Section: Discussionmentioning
confidence: 99%
“…The story of tea starts in China in 2737 BC. China remians the largest tea producer with an output of 1.9 million tons annually [5,6] with more than 100 officially approved tea cultivars in 15 provinces [7,8]. Xinyang maojian tea is one of the Chinese traditional famous teas with a specific flavor.…”
Section: Introductionmentioning
confidence: 99%
“…Xinyang maojian tea is one of the Chinese traditional famous teas with a specific flavor. Some evidence indicates that these specific flavors are highly related to the abundance of specific secondary metabolites such as polyphenols, theanine, caffeine, vitamins, volatile oils, polysaccharides, and minerals [2,3,6]. Among these metabolites, polyphenols, caffeine, and theanine are usually considered as distinctive functional compounds, which play key roles in the formation of special taste, as well as nutritional and medicinal properties [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This range might be due to genetic effects on nitrogen metabolism in the different tea cultivars. 27,28 Since 13 C and 15 N values are expected to be influenced by genetic factors, this data could provide some useful information for future sampling strategies and for discussions on determining the geographic origins of teas by IRMS. In some plant-derived foods, like potato, the variety does impact the stable isotope composition, 5 but it is not a significant (P > 0.05) factor in pistachios.…”
Section: And 15 N Valuesmentioning
confidence: 99%